A Model for Improving Occupational Safety and Health Based on Ergonomics in Construction Projects - I Nengah Darma Susila; I Ketut Sutapa; I Wayan Pugra; I Made Jaya; I Wayan Sudiasa (Universitas Pendidikan Nasional, 2026)
Construction workers are frequently exposed to falls, struck-by hazards, manual material handling, awkward postures, repetitive movements, and environmental stressors that may affect occupational safety, health, and productivity. This study integrates occupational safety and health (OSH) risk assessment with ergonomic risk factor evaluation to identify priority controls for building construction work. A descriptive cross-sectional design was applied to selected building projects in Badung, Denpasar, and Tabanan, Bali. Fifty workers and construction personnel were selected using purposive sampling because of their direct involvement in the observed activities. Primary data were collected through field observations, structured interviews, and closed questionnaires, while project records and relevant standards were used as secondary data. Fifty hazards associated with 18 work activities were assessed using modal likelihood and consequence scores. Ergonomic exposures were evaluated using the components of SNI 9011:2021 covering the upper body, back and lower body, and manual load handling. The risk assessment identified 2 low-risk hazards (4%), 14 moderate-risk hazards (28%), and 34 high-risk hazards (68%). The average ergonomic risk factor score by district was 44.89, while the average score by job type was 38.31; all assessed groups exceeded the hazardous threshold. Upper-body exposure was the largest contributor, followed by back/lower-body exposure and manual load handling. Existing controls were dominated by personal protective equipment and were insufficient to address the sources of ergonomic risk. An improvement framework is therefore proposed that prioritizes elimination or substitution, engineering controls, administrative controls, task-specific PPE, and periodic reassessment. The findings provide a structured basis for contractors to prioritize ergonomic and OSH interventions, although the proposed controls require post-implementation evaluation in future research.